Revitalising EU-ACP cooperation : how decentralised cooperation can contribute to poverty eradication in Africa - Vashee, Basker (ECDPM MaastrichtNL, 1997)
Illustrates, with examples from Ethiopa, Guinea-Bissau, Ghana, Uganda, Tanzania and South Africa, the type of projects that should be encouraged in the rubic of decentralised cooperation and poverty eradication.